Montenegro : Financial Sector Assessment Program-Banking Supervision and Regulation-Technical Note. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses the current status of banking supervision and regulation in Montenegro in the context of select Basel Core Principles. It provides a brief overview of the financial system structure, bank system performance, and the framework for financial oversight. Laws, regulations, and supervision have improved significantly since the 2006 Financial Sector Assessment Program to align more closely with Basel and EU requirements. The banking sector dominates the financial system and accounts for about 90 percent of financial system assets, equivalent to about 93 percent of GDP as of June 2015. There are currently 14 banks operating in Montenegro, up from 11 in 2013.